Kinerja Ombudsman Republik Indonesia Perwakilan Jakarta Raya Dalam Menangani Pengaduan Penerimaan Peserta Didik Baru Di Kota Depok - Nurlita Purnama; Annisa Miskiyah; Reza Rizkynata; Muhammad Khairul Anwar (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research is based on the large number of public reports that have been submitted to the Greater Jakarta Ombudsman regarding allegations of maladministration that have occurred in the education sector, especially complaints about New Student Admissions. This problem requires a resolution by the Greater Jakarta Ombudsman to handle public complaints and prevent recurring maladministration in the education sector, especially regarding complaints about Acceptance of New Students in Depok City. This study aims to analyze and describe the performance of the Greater Jakarta Ombudsman in handling complaints about Acceptance of New Students in Depok City. This is based on the problems that occurred in the implementation of the Acceptance of New Students which were still colored by allegations of maladministration, which made public services in the field of education inefficient, lack of supervision in the implementation of the acceptance of new students. The results of the study concluded that in the Productivity indicator there are still a number of things that need to be improved such as policies that have been made that are not in accordance with the needs of society in the digitalization era. Service Quality Indicators still need a number of things to pay attention to such as budget constraints, human resources and very limited work space. Responsiveness Indicators There are still a number of things that affect performance achievements. The Responsibility Indicator is still lacking in realization to achieve the target every year. As well as the Accountability indicator, there is still no specific accountability report in the form of the Jakarta Raya Ombudsman annual report on various media platforms.